Challenges faced in the process of inclusion of individuals with autistic spectrum disorder at the university scope (Research, Society and Development, 2021)
Introduction: Autistic Spectrum Disorder (ASD) designates numerous manifestations related to deficiencies in communication and social interaction. Due to the great insertion of these individuals in the university environment, it is necessary to understand how this process occurs, as well as what challenges are experienced. Objective: To discuss and list the main challenges in the inclusion process faced by individuals with ASD in the context of higher education. Methods: This is an integrative review, where searches were carried out in the electronic databases Scielo, Lilacs, VHL and MedLine, using the descriptors according to the DeSC, published between 2017 and 2021. To compose the results, seven articles were selected according to with the inclusion and exclusion criteria previously established. Results: The main challenges faced by individuals with ASD in the inclusion process are anxiety, depression, fear, lack of understanding by the faculty, difficulties in adapting teaching methodologies, difficulty in socialization, as well as stigma and lack of individualized support. , not being respected the singularities of each individual. Conclusion: Even with the growing number of students with ASD in universities, the difficulties faced are still evident, as well as the limitations presented by HEIs to deal with this audience, so it is necessary to adopt measures that are able to prioritize these individuals.